Towards secure and resilient unmanned aerial vehicles swarm network based on blockchain - Xin Zhou; Lin Yang; Linru MA; Huasen He (IET Blockchain)
Abstract Blockchain, as an emerging technology, has found diverse applications in solving trust issues in multi‐party cooperation. The field of Unmanned Aerial Vehicle (UAV) swarm networks is no exception, as UAVs are susceptible to attacks from malicious counterparts due to limited computing and storage resources. In this paper, the authors present an adaptive networking mechanism for UAVs based on blockchain technology, which incorporates three key technologies. Utilizing Global Unique Identifier (GUID) and block storage, UAVs can achieve rapid identity authentication and efficient swarm switching. By evaluating node participation in block consensus, malicious nodes within the UAV swarm can be accurately identified. Additionally, routing learning based on node security attributes and link quality ensures secure and efficient data transmission. Simulation test results demonstrate the practicality and applicability of the proposed blockchain‐based adaptive networking mechanism for UAV swarm networks.